The effects of endothelin receptor blockade by bosentan on the healing of a bowel anastomosis in an experimental Crohn's disease model - Kirkil, Cuneyt; Cetinkaya, Ziya; Ustundag, Bilal; Akpolat, Nusret; Ayten, Refik; Bulbuller, Nurullah (Springer, 2008)
Objective It was previously described that endothelins may contribute to the pathogenesis of Crohn's disease. In this study, it was aimed to investigate the effects of endothelin receptor blockade by bosentan on the healing of a bowel anastomosis in an experimental Crohn's disease model. Material and Methods Twenty-eight Sprague-Dawley rats were divided into four groups. Groups I and II were used as sham-operated and control groups, respectively. Bowel inflammation induced by intrajejunal injection of iodoacetamide in groups III and IV. Rats in group IV were treated with oral preparation of bosentan 60 mg/kg/day. Three days after induction of the inflammation, partial resection of test loop and anastomosis was performed. Re-laparotomy was performed, anastomosis bursting pressures and peritonitis scores were measured, and tissue samples were obtained for the measurements of tissue hydroxylproline level and mucosal damage index 4 days later. Results The mean mucosal damage index and peritonitis score of group IV were significantly lower, and the mean tissue hydroxyproline level and anastomotic bursting pressure of group IV were significantly higher than those of group III. Conclusion The blockade of endothelin receptors by bosentan decreases the severity of iodoacetamide induced intestinal inflammation, increases the wound healing in the inflamed intestinal tissue, and decreases the severity of peritonitis.
Keywords: Crohn's disease; endothelin; bosentan; wound healing; intestinal anastomosis